Antimicrobial Usage in Companion and Food Animals: Methods, Surveys and Relationships with Antimicrobial Resistance in Animals and Humans - Ángel Moreno, Miguel; Collineau, Lucie; Anne Carson, Carolee (Frontiers Media SA, 2020)
Antimicrobial resistance (AMR) is currently a high priority topic for public health and a paradigmatic example of the One Health concept. AMR bacteria flow among humans and animals and actions for fighting the problem must take into account both sectors. Antimicrobial usage (AMU) is one of the potential drivers for AMR. In the animal sector, many national and supra-national authorities (e.g. the European Medicines Agency) have established AMU monitoring programs, most of them being based on sales data of antimicrobials for veterinary use. While providing very valuable information, these data also have limitations and make it difficult to identify by whom, when and how the antimicrobial products were actually used. Different central aspects of AMU monitoring remain to be solved, including, among others: full coverage of both companion and food animal, use of appropriate methods for collection of information at the animal and farm levels and choice of metrics of measurement of AMU and animal populations at risk.